PATUNG GANESA: SUATU KAJIAN TEOLOGI HINDU - Kadek Bayu Indrayasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Installation of Ganesh sculpture around the homes of Hindu community in Bali isincreasingly found. The meaning of society on the installation of the sculpture and even thenvaried. Some interpreted as a form of abuse, by reason of putting the sacred madhab of sacredBuddhism in place in an unholy place, not in the main mandala; there are also communitygroups that make positive on the grounds, Ganesha as a rescue deity so it is feasible to bemanifested in the homes of the residents to beg for protection, safety. This meaningless discrepancygave birth to the desire to examine the Ganesha statue from the perspective of Hindu theology.The question is how the concept of the deity of Ganesha statue?The Ganesha sculpture researchfrom the perspective of Hindu theology is done through a number of literature, which is associatedwith ritual functions and meanings associated with Ganesh statues. The results of the studyfound that the installation of Ganesha statues in a number of Hindu homes in Bali is a hope ofsalvation, through the protection of Ganesha in the function of the patron god of his people.